DOES ENVIRONMENTALLY FRIENDLY AND HALAL PRODUCTS IMPACT MUSLIM CONSUMERS PURCHASE INTENTION? EVIDENCE IN DKI JAKARTA: Apakah Produk Ramah Lingkungan dan Halal Mempengaruhi Niat Beli Konsumen Muslim? Bukti Empiris dari DKI Jakarta - Adly Azra Hamami; An'im Kafabih (Jurnal Ilmu Keluarga dan Konsumen, 2025)
The limited availability of environmentally friendly halal products in Indonesia highlights the need to examine factors that shape consumer purchase intentions. This study investigates key determinants influencing Muslims’ purchase intention toward products that meet both halal and environmental standards. Using data from 215 Muslim consumers in DKI Jakarta, collected through online and offline purposive sampling, the analysis was conducted with SEM-PLS. The results show that halal green awareness and attitude influence purchase intentions. Meanwhile, halal labels, eco-labels, environmental knowledge, and religiosity affect halal green awareness and attitudes. In this study, piety is also found to influence religiosity. Overall, the findings indicate that halal labels, eco-labels, environmental knowledge, piety, and religiosity shape halal green awareness and attitudes, which in turn influence Muslims’ purchase intentions toward environmentally friendly halal products in DKI Jakarta. Future research may incorporate variables such as price, product quality, and digital media influence to provide a more comprehensive understanding of consumer behavior in this context.